2015
DOI: 10.1038/cddis.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Neuritin 1 promotes retinal ganglion cell survival and axonal regeneration following optic nerve crush

Abstract: Neuritin 1 (Nrn1) is an extracellular glycophosphatidylinositol-linked protein that stimulates axonal plasticity, dendritic arborization and synapse maturation in the central nervous system (CNS). The purpose of this study was to evaluate the neuroprotective and axogenic properties of Nrn1 on axotomized retinal ganglion cells (RGCs) in vitro and on the in vivo optic nerve crush (ONC) mouse model. Axotomized cultured RGCs treated with recombinant hNRN1 significantly increased survival of RGCs by 21% (n=6–7, P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 76 publications
1
33
0
Order By: Relevance
“…Neuritin overexpression induces the recovery of crushed optic nerve in mouse (Sharma et al, 2015). We recently showed that recombinant Neuritin protects neurons against apoptosis following spinal cord injury (Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Neuritin overexpression induces the recovery of crushed optic nerve in mouse (Sharma et al, 2015). We recently showed that recombinant Neuritin protects neurons against apoptosis following spinal cord injury (Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, RGC markers had the highest downregulation fold changes, as for example, peripherin (-12.7x), neurofilament heavy, medium and light polypeptides (-11.4x, -11.8x and -6.8x, respectively), gamma synuclein (-10.8x), POU class 4 homeobox 2 (or Brn3A, -7.3x), Thy-1 cell surface antigen (-3.9x), synaptotagmin II (-2.4x), tubulin, beta 3 class III (-1.9x), internexin neuronal intermediate filament protein (-1.9x), alpha-internexin (-1.9x) and pannexin 2 (-1.89x). In addition, the retinal ganglion cell neurotrophic factor neuritin 1 [59] was also strongly down-regulated after ONC, with a -18.8x decrease when compared to controls ( Figure 2B). The EnrichR software, a tool to determine disease-enriched perturbations in the transcriptome that uses the GEO database, showed that among the down-regulated genes at 14 days after ONC, the top disease signature was "Glaucoma associated with systemic syndromes" (Table S4).…”
Section: Transcriptomic Alterations In Rat Retina After Optic Nerve Cmentioning
confidence: 92%
“…JAK/STAT, PI3K/Akt and MAPK/ERK. 49,50 This can be achieved for example by deletion of Krüppel-like family of transcription factors (KLF), 51 osteopontin, 52 phosphatase and tensin homolog (PTEN) 44,53,54 and/or suppressor of cytokine signaling 3 solution (SOCS3), 53,54 activation of the mechanistic target of rapamycin (mTOR) signaling pathway, 52,55 administration of Rho kinase (ROCK) inhibitors, 56 overexpression of glycogen synthase kinase 3 (GSK3), 57 c-myc, 58 neuritin-1, 59 or thrombospondin.-1 60 From recent studies, it is clear that multiple strategies that focus on both extrinsic and intrinsic factors should be combined to maximize axon outgrowth. 37,38,44,[61][62][63][64] For example, intraocular inflammation, cAMP, and PTEN deletion were found to act synergistically to augment regeneration.…”
Section: The Retinofugal System As a Model To Study Axonal Regenerationmentioning
confidence: 99%